DAMPAK IMPLEMENTASI ARTIFICIAL INTELLIGENCE (AI) TERHADAP EFISIENSI PRODUKSI PADA INDUSTRI ELEKTRONIK DI INDONESIA - Listari, Endang; Maharani, Amelia Pepri; Nopitasari, Lira; Nuraini, N; Sundari, Afifa (Pusat Riset dan Publikasi, 2025)
The electronics industry, as a vital part of the manufacturing sector in Indonesia, faces productivity and competitiveness challenges amidst global pressures and technological disruption. In this situation, the application of intelligent technology such as Artificial Intelligence (AI) is a strategic alternative to increase efficiency in the production line. Therefore, this study aims to examine the impact of the implementation of Artificial Intelligence (AI) on production efficiency in the electronics industry in Indonesia. This article used a qualitative data analysis with descriptive methods and through a literature review approach. The results of this study showed that Artificial intelligence (AI) brings transformations in operational management with the potential to increase efficiency. The application of AI can improve production efficiency through work process automation, real-time defect detection, and data-driven planning optimization. This technology allows for reduced operational costs, improved product quality, and accelerated production times. However, the implementation process is not without various obstacles, such as limited digital infrastructure, a lack of competent human resources, and high initial investment costs. Therefore, the success of AI implementation depends heavily on internal company readiness and ongoing policy support. This research provides strategic insights for the development of an intelligent technology-based electronics industry in Indonesia.